Mars‐solar wind interaction: LatHyS, an improved parallel 3‐D multispecies hybrid model. Issue 7 (15th July 2016) - Modolo, Ronan; Hess, Sebastien; Mancini, Marco; Leblanc, Francois; Chaufray, Jean‐Yves; Brain, David; Leclercq, Ludivine; Esteban‐Hernández, Rosa; Chanteur, Gerard; Weill, Philippe; González‐Galindo, Francisco; Forget, Francois; et al.
Abstract: In order to better represent Mars‐solar wind interaction, we present an unprecedented model achieving spatial resolution down to 50 km, a so far unexplored resolution for global kinetic models of the Martian ionized environment. Such resolution approaches the ionospheric plasma scale height. In practice, the model is derived from a first version described in Modolo et al. (2005). An important effort of parallelization has been conducted and is presented here. A better description of the ionosphere was also implemented including ionospheric chemistry, electrical conductivities, and a drag force modeling the ion‐neutral collisions in the ionosphere. This new version of the code, named LatHyS (Latmos Hybrid Simulation), is here used to characterize the impact of various spatial resolutions on simulation results. In addition, and following a global model challenge effort, we present the results of simulation run for three cases which allow addressing the effect of the suprathermal corona and of the solar EUV activity on the magnetospheric plasma boundaries and on the global escape. Simulation results showed that global patterns are relatively similar for the different spatial resolution runs, but finest grid runs provide a better representation of the ionosphere and display more details of the planetary plasma dynamic. Simulation results suggest that a significant fraction of escaping O + ions is originated from below 1200 km altitude. Key Points: A new 3‐D parallelized multispecies hybrid code for Mars‐SW interaction A parametric study to determine the influence of the spatial resolution on the simulation results Investigation of the importance of the extended exosphere on Mars's plasma escape